Associations of long-term exposure to ambient PM2.5 with mortality in Chinese adults: A pooled analysis of cohorts in the China-PAR project. (May 2020) - Yang, Xueli; Liang, Fengchao; Li, Jianxin; Chen, Jichun; Liu, Fangchao; Huang, Keyong; Cao, Jie; Chen, Shufeng; Xiao, Qingyang; Liu, Xiaoqing; Shen, Chong; Yu, Ling; et al.
Highlights: Combining satellite-based PM2.5 levels with cohort data in general Chinese adults. A broad range of long-term exposure to PM2.5 from 31 μg/m 3 to 97 μg/m 3 . A weak exponential curve observed between long-term PM2.5 exposure and mortality. Abstract: Background: The concentration-response relationship between mortality and long-term exposure to fine particulate matter (PM2.5 ) has not been fully elucidated, especially at high levels of PM2.5 concentrations. Objective: We aimed to evaluate chronic effects of ambient PM2.5 exposure on deaths among Chinese adults in high-exposure settings. Methods: Participants of the Prediction for Atherosclerotic cardiovascular disease Risk in China (China-PAR) project were included from four prospective cohorts among Chinese adults aged ≥18 years old. The overall follow-up rate of the four cohorts was 93.4% until the recent follow-up survey that ended in 2015. The average of satellite-based PM2.5 concentrations during 2000–2015 at 1-km spatial resolution was assigned to each participant according to individual residence addresses. Based on the pooled analysis of individual data from the four cohorts, a Cox proportional hazards model was used to estimate the hazard ratio (HR) and corresponding 95% confidence intervals (95% CIs) for the association of PM2.5 exposure with mortality after multivariate adjustment. Results: A total of 116, 821 participants were eligible in the final analysis. During a mean of 7.7 years of follow-up, 6, 395 non-accidental deaths and 2, 507 cardio-metabolic deaths occurred. The mean of PM2.5 concentration was 64.9 μg/m 3 ranging from 31.2 μg/m 3 to 97.0 μg/m 3 . For each 10 μg/m 3 increment in PM2.5, the HR was 1.11 (95% CI: 1.08–1.14) for non-accidental mortality and 1.22 (95% CI: 1.16–1.27) for cardio-metabolic mortality. In addition, a weak exponential curve for the concentration-response association between mortality and PM2.5 was observed among Chinese adults. Conclusions: Our study provided important evidence of the long-term effects of PM2.5 exposure on deaths among Chinese adults. The findings expand our knowledge on concentration-response relationship in high-exposure environments, which is essential to address the urgent challenge of reducing the disease burden attributable to PM2.5 exposure in rapidly industrializing countries such as China.